Effects of a stocking on plantar sensation in individuals with and without ankle instability. Issue 4 (26th December 2016) - Burcal, Christopher J.; Hoch, Matthew C.; Wikstrom, Erik A.
ABSTRACT: Introduction: It is unknown whether footwear has a beneficial or deleterious effect on cutaneous sensitivity. We aimed to test a preliminary model of footwear and its effect on tactile perception among groups of controls, copers, and chronic ankle instability participants. Methods : Light‐touch thresholds were obtained for 45 participants (age: 20.2 ± 2.8 years; height: 167.6 ± 9.8 cm; mass: 66.3 ± 14.7 kg) using Semmes‐Weinstein monofilaments at the head of the first metatarsal (1MT), base of the fifth metatarsal (5MT), and calcaneus (CAL). Baseline measurements were compared with those taken after wearing a nylon stocking for 5 min. Results : Thresholds were increased at all 3 sites when the stocking was worn ( P < 0.05). Controls had an increase at 1MT, copers had an increase at 5MT and CAL, and chronic ankle instability had an increase at CAL. Conclusions : Cutaneous thresholds increase when subjects wear a nylon stocking, a model for the sensory effects of footwear. A history of ankle injury appears to influence which sites have altered sensibility. Muscle Nerve, 2016. Muscle Nerve 55 : 513–519, 2017